This preview shows page 1. Sign up to view the full content.
Unformatted text preview: ( k ) ≤ n + 2 n n1 X k =1 ck lg k (inductive hypothesis) = n + 2 c n b n/ 2 c X k =1 k lg k + n1 X k = b n/ 2 c +1 k lg k ≤ n + 2 c n b n/ 2 c X k =1 k lg n 2 + n1 X k = b n/ 2 c +1 k lg n = n + 2 c n (lg n1) b n/ 2 c X k =1 k + lg n n1 X k = b n/ 2 c +1 k = n + 2 c n lg n n1 X k =1 kb n/ 2 c X k =1 k ≤ n + 2 c n ± n 2 lg n 2b n/ 2 c ( b n/ 2 c 1) 2 ² ≤ n + 2 c n ± n 2 lg n 2( n/ 3) 2 2 ² = cn lg ncn 9 + n ≤ cn lg n provided c ≥ 9. 1...
View
Full
Document
This note was uploaded on 12/13/2011 for the course CSCE 750 taught by Professor Fenner during the Fall '11 term at South Carolina.
 Fall '11
 Fenner
 Algorithms, Sort

Click to edit the document details